Fenomena Tumpeng Kering Ready Stock Dalam Sistem Upakara Hindu Di Bali - Ayu Veronika Somawati; Ni Wayan Wiraswastini (Purwadita : Jurnal Agama dan Budaya, 2021)
Hinduism with all its uniqueness basically cannot be separated from acara as a part of the Tri Framework for Hindu Religion, as well as the use of ceremonial facilities as a medium to get closer to the Creator. One of the means of upakara that is often found in Hindu religious practice is the use of tumpeng. Tumpeng is one of the upakara ingredients in the shape of a cone made from rice. The higher the human mobility, the less time that can be devoted to the preparation of religious events. Things like this are ultimately used as business land. Like the current phenomenon, it is common to find the use of dried tumpeng in the manufacture of upakara. This type of tumpeng is usually very easy to find in the market and some are even traded online at very affordable prices. Apart from being cheap, the tumpeng dries up a solution for Hindus who do not have enough time to make this upakara. Keywords: Tumpeng, Upakara, Hindu, Bali